Investigating a Hampered NRE Utilization in Kaltim’s Energy System: Is there an Energy Policy with a Syndrome of the Energy-abundant Area? - Novena Damar Asri; Purnomo Yusgiantoro (International Journal of Renewable Energy Development, 2021)
Kaltim presumably experiences an energy paradox, where the energy system is unreliable and unsustainable, despite energy-rich. This study presumes that the paradox is caused by the ‘ill-advised energy policy’ shown by ‘energy-area incompatibility’ that is exacerbated by the ‘energy-rich syndrome’ (a mindset of feeling secure due to energy-abundance leading to a wasteful behavior). This study investigates the indication of the syndrome in Kaltim energy policy by first investigating ‘the incompatibility’ and its impacts by examining Kaltim’s geographical characteristics, energy potential, population-distribution, electricity system, and infrastructure. Also, the impacts of retaining the syndrome through cost analyses. This study finds the incompatibility between energy-sources utilization and geographical characteristics, by conducting a descriptive method with data collection and analyses. Kaltim is forest-dominated with scattered-population, suitable with an off-grid system. However, the electricity development is mostly on-grid, fossil-based designed, explaining the difficulties of electrifying the entire Kaltim, although electricity is surplus. While off-grid should be applied to NRE, the massive use of diesel-gen-sets shows wasteful behavior. By conducting a linear-regression method, this study finds that Kaltim’s electricity consumption (indicating the infrastructure sufficiency) is lower than it should be, given its incredible economic performance. The incompatibility causes infrastructure insufficiency. The cost analysis finds that the massively-used fuel oil is the most expensive. The subsidy would be around 0.003%-0.275% of Kaltim GDRP or 17 billion-1.55 trillion IDR. As the new Capital location, NRE is a must for Kaltim. To conclude, NRE utilization is very low, although its potential is huge, and Kaltim’s forested characteristics suit it. NRE only covers 3% of Kaltim’s electricity, while the potential (hydro alone) is more than 6,900MW. The incompatibility causes an unreliable electricity system, although electricity is surplus. Following Kaltim’s geographical characteristics, NRE should be optimized. This study intends to aware the policy-makers of the syndrome, thereby develop a ‘proper energy policy’.